Identitas Sosial Orang Minangkabau yang Keluar dari Islam - Afif, Afthonul (Jurnal Psikologi, 2009)
The Minangkabau custom did not allow Minangkabaunese for converting Islam into another religion. Minangkabau custom will apply particular sanction for them who disobey the dictum. This research aimed to know how the dynamic of social identity construction of disserted Minangkabau peoples was, what the motive behind the decision in leaving Islam was, and what cultural impacts were. This research employed inâ€depth interview for collecting data, involving five (5) respondents. This research used phenomenology method in capturing and understanding the natural meaning in respondents living. The validity of data was achieved through intersubjective validity. The result of this research showed that disserted Minangkabaunese have experienced the discriminative actions from their community such as being isolated by their community thus they experienced the crises of identity. Their right of family treasure was also canceled by their family. These circumstance has become a trigger for constructing â€œthe another Minangkabau identityâ€ which was not solely decided by status as a Moslem. Eventhough their family and community have rejected them as a part of Minangkabau community, they remain assumed theirself as the Minangkabau people because they inherit Minangkabau blood.